Organizational structures of companies versus project management effectiveness - Joanna Haffer (Torun Business Review, 2012)
An organizational structure, indicated as one out of the four main organizational conditions supporting project management, has an essential meaning for project execution. This article, based on the research results, describes different organizational structures of project-orientated enterprises, enumerating their advantages and disadvantages, and reveals the influence of inter-organizational relations on project management effectiveness in enterprises operating in Poland. The results indicate that the more a character of inter-organizational relations is heading towards project structure, the higher project management effectiveness is. In the next sequence the project management processes are supported by strong matrix structures, whereas the worst outcomes are provided by functional structures. Simultaneously, it was concluded that project structures are conducive to high advancement of project management processes, and among them, especially project risk management processes as well as communication, time and cost management processes.